PJMHS 2022
DOI: 10.53350/pjmhs22164554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Oral Pathologies Associated with Second Molars to the Patterns of Adjacent Impacted Third Molar

Abstract: Objective: To assess the relationship of oral pathologies associated with second molars to the patterns of adjacent impacted third molar. Methodology: A cross sectional descriptive study was conducted on 385 Orthopantomograms (OPG) of patients. The study was conducted in the Institute of Dentistry, CMH Lahore Medical College, Lahore, Sharif Medical and Dental College (SMDC) and Services Institute of Medical Sciences (SIMS) over a period of three months from December 2020 to February 2021. The Pell and Gregor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…While the incidence of periapical radiolucencies in mandible was reported to be 44.3% and documented pericoronal radiolucencies were 0.4%. 10 This study concluded that the carious lesions associated with the second molar adjacent an impacted third molar were higher in the mandible (13.8%) in comparison to the maxilla (1.2%). This rate of carries was less than a study by Kumar in which it has been reported that the caries was strongly linked to adjacent mandibular and maxillary second molars (32.20 % and 33.90 %, in both).…”
Section: Discussionmentioning
confidence: 77%
“…While the incidence of periapical radiolucencies in mandible was reported to be 44.3% and documented pericoronal radiolucencies were 0.4%. 10 This study concluded that the carious lesions associated with the second molar adjacent an impacted third molar were higher in the mandible (13.8%) in comparison to the maxilla (1.2%). This rate of carries was less than a study by Kumar in which it has been reported that the caries was strongly linked to adjacent mandibular and maxillary second molars (32.20 % and 33.90 %, in both).…”
Section: Discussionmentioning
confidence: 77%